2020
DOI: 10.1364/boe.404101
|View full text |Cite
|
Sign up to set email alerts
|

Optical monitoring of cerebral perfusion and metabolism in adults during cardiac surgery with cardiopulmonary bypass

Abstract: During cardiac surgery with cardiopulmonary bypass (CPB), adequate maintenance of cerebral blood flow (CBF) is vital in preventing postoperative neurological injury – i.e. stroke, delirium, cognitive impairment. Reductions in CBF large enough to impact cerebral energy metabolism can lead to tissue damage and subsequent brain injury. Current methods for neuromonitoring during surgery are limited. This study presents the clinical translation of a hybrid optical neuromonitor for continuous intraoperative monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…The NNeMo system combines hsNIRS and DCS by incorporates a multiplexing shuttering system to cycle between acquisitions from the two subsystems 29 , 30 . For this study, hsNIRS and DCS data were each acquired at a sampling frequency of 4 Hz in consecutive 3-s intervals, resulting in full data sets every 7 s (with a 0.5-s dead-time between subsystems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NNeMo system combines hsNIRS and DCS by incorporates a multiplexing shuttering system to cycle between acquisitions from the two subsystems 29 , 30 . For this study, hsNIRS and DCS data were each acquired at a sampling frequency of 4 Hz in consecutive 3-s intervals, resulting in full data sets every 7 s (with a 0.5-s dead-time between subsystems).…”
Section: Methodsmentioning
confidence: 99%
“…Combining hsNIRS with DCS offers the ability to evaluate the impact of fluctuations in CBF on cellular oxygen metabolism. Considering that cerebral energy requirements can be maintained during reductions in CBF by a compensatory increase in oxygen extraction 27 29 , detecting concurrent reductions in CBF and oxCCO could be of greater clinical significance—indication of possible hypoxia—than changes in perfusion or oxygenation alone.…”
Section: Introductionmentioning
confidence: 99%
“…The found that the information provided by these devices was able to help achieve patient specific optimal brain perfusion (Zavriyev et al, 2021). In a similar study, Rajaram et al (2020) explored the hybrid NIRS system that combined DCS and fixed wavelength NIRS to examine CBF and the cerebral oxidation state of CCO in 10 patients undergoing cardiac surgery with cardiopulmonary bypass. Once again, they found that this intraoperative NIRS based multimodal monitoring aided in the real-time assessment of patient specific cerebral hemodynamics (Rajaram et al, 2020).…”
Section: Near-infrared Spectroscopy In Intraoperative Monitoring Of Traumatic Brain Injury Patientsmentioning
confidence: 99%
“…Clinical studies have shown the ability of hsNIRS to detect oxCCO changes associated with neonatal hypoxic-ischemic encephalopathy, preterm birth, and cardiac surgery. 21 25 …”
Section: Introductionmentioning
confidence: 99%